Integrating the virtual platform Memrise as a teaching tool for english vocabulary in foreign language students of second semester at a university. - Heriberto González Valencia; German Darío Isaza Gómez; Mayra Alexandra Idarraga; Michelle Rodríguez Villaquiran (Universidad de Caldas, 2020)
This research was done to arise students and teachers consciousness about the importance of integrating technology, which allows students to keep learning and improving out of their class time. The objective was to determine the effect of integrating the virtual platform Memrise as a teaching tool. The methodology used a quantitative approach that aims to better understand the results measurement, based on the information obtained from the pre-test, post-tests and Memrise's database. The context was a program of foreign languages at a Colombian University in the 2018B period for students of the second semester of a Foreign Languages program, integrating the virtual platform Memrise. The conclusion was that the effect of integrating the virtual platform Memrise as a teaching tool for English vocabulary was effective, even though this application was not interesting or easy to use for some students.